Company Legislation and Changing Patterns of Disclosure in British Company Accounts 1900-1940 (Book). - Meyer, Philip E.; Lee, Thomas A. (The Accounting Review, 1982)
Reviews the book "Company Legislation and Changing Patterns of Disclosure in British Company Accounts, 1900-1940," by J.R. Edwards.